FUZZY PORTFOLIO OPTIMIZATION USING QUADRATIC PROGRAMMING - Menekay, Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the arrangement of fuzzy portfolio advancement utilizing the Lagarrange multiplier technique. The definition of the nonlinear improvement model for the portfolio advancement issue and its answer are given. As information for portfolio improvement, the recorded returns of benefits and estimations of expected returns are taken. At the point when portfolio improvement issues are portrayed with vulnerability and adaptability in issue imperatives, the fuzzy sets are an appropriate portrayal for demonstrating this kind of enhancement issue. The detailing of the fluffy portfolio advancement issue and its answer are given. The level method is utilized to characterize vitality work for fuzzy portfolios and find ideal fuzzy estimations of the protections.